Rhetorical Value of Russian Inserts in the Posts by Lithuanian Politicians on “Facebook” - Gabrėnaitė, Eglė; Biržietienė, Skirmantė (Information & Media, 2023)
The article presents the study of political communication on social network “Facebook”. The object of the study is the motivation of using Russian inserts and potential influence on the effectiveness of the discourse. Effectiveness is related to the persuasion, the goal of the addressee in the communication process and the main concept of rhetoric, therefore, a rhetorical discourse analysis was used for the research. The focus of the presented research is on Russian language inserts in the posts by Lithuanian politicians published on the social network “Facebook”. The purpose of the research is to discuss the rhetorical value of Russian inserts. Inserts are elements of another language inserted into the main language, in this case Russian words (both authentic and adapted form), parts of words, text fragments. After examining over 100 Russian language inserts in the records of native Lithuanian politicians, two trends have emerged: 1) Russian language inserts in politicians’ records are deliberately used as means of stylistic expression, helping to imitate natural, informal speech, as well as creating contextual discourse; 2) Russian language is used as a way to express political attitudes and value positions.